Overexpression of PY1289-HER3 in sporadic pulmonary carcinoid from patients bearing MEN1 gene variants - LATTANZIO, ROSSANO (Oncol Lett, 2016)
The present study aimed to investigate the expression of human epidermal growth factor receptors (HERs) (HER1/HER2/HER3/HER4) and their phosphorylated forms (p-HER1/p-HER2/p-HER3/p-HER4) in pulmonary carcinoids (PCs). HER and p-HER protein expression was assessed by immunohistochemistry on tissue microarrays in 37 specimens of sporadic PCs, 29 typical carcinoids (TCs) and 8 atypical carcinoids (ACs). When compared with the ACs, the TCs did not exhibit any differences in terms of HER/p-HER expression. The tumors of this study have previously been characterized for the expression of menin and the mutational status of menin 1 (MEN1), a gene strongly implicated in the pathogenesis of PCs. In the present study, it was found that the cytoplasmic (‘disarrayed’), but not nuclear (‘arrayed’) expression of menin was positively correlated with HER3 (P=0.004), HER4 (P=0.015), p-HER1 (P=0.005), p-HER3 (P<0.001), and p-HER4 (P=0.001) expression. Moreover, HER3 and p-HER3 were found to be significantly more expressed in PCs with MEN1 variants, than in tumors with MEN1 wild-type (P=0.000 and P=0.025, respectively). These findings suggest the potential clinical use of HER inhibitors in the treatment of patients with PCs, particularly for individuals with p-HER3-positive PCs harboring MEN1 gene variants.